Effect of a one-time financial incentive on linkage to chronic hypertension care in Kenya and Uganda: A randomized controlled trial. - Matthew D Hickey; Asiphas Owaraganise; Norton Sang; Fredrick J Opel; Erick Wafula Mugoma; James Ayieko; Jane Kabami; Gabriel Chamie; Elijah Kakande; Maya L Petersen; Laura B Balzer; Moses R Kamya; et al. (PLoS ONE, 2022)
Background Fewer than 10% of people with hypertension in sub-Saharan Africa are diagnosed, linked to care, and achieve hypertension control. We hypothesized that a one-time financial incentive and phone call reminder for missed appointments would increase linkage to hypertension care following community-based screening in rural Uganda and Kenya. Methods In a randomized controlled trial, we conducted community-based hypertension screening and enrolled adults ≥25 years with blood pressure ≥140/90 mmHg on three measures; we excluded participants with known hypertension or hypertensive emergency. The intervention was transportation reimbursement upon linkage (~$5 USD) and up to three reminder phone calls for those not linking within seven days. Control participants received a clinic referral only. Outcomes were linkage to hypertension care within 30 days (primary) and hypertension control <140/90 mmHg measured in all participants at 90 days (secondary). We used targeted minimum loss-based estimation to compute adjusted risk ratios (aRR). Results We screened 1,998 participants, identifying 370 (18.5%) with uncontrolled hypertension and enrolling 199 (100 control, 99 intervention). Reasons for non-enrollment included prior hypertension diagnosis (n = 108) and hypertensive emergency (n = 32). Participants were 60% female, median age 56 (range 27-99); 10% were HIV-positive and 42% had baseline blood pressure ≥160/100 mmHg. Linkage to care within 30 days was 96% in intervention and 66% in control (aRR 1.45, 95%CI 1.25-1.68). Hypertension control at 90 days was 51% intervention and 41% control (aRR 1.22, 95%CI 0.92-1.66). Conclusion A one-time financial incentive and reminder call for missed visits resulted in a 30% absolute increase in linkage to hypertension care following community-based screening. Financial incentives can improve the critical step of linkage to care for people newly diagnosed with hypertension in the community.